RISK MANAGEMENT IN STUDENT MANAGEMENT: EFFORTS TO IMPROVE THE QUALITY OF EDUCATION AT MI MANBA'UL HUDA BANDUNG CITY - Asri Sulastri; Mulyawan Safwandy Nugraha (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
Based on data obtained from the Programe for International Student Assessment (PISA) in 2022 regarding the decline in the quality of education in Indonesia, which is reviewed from literacy, numeracy, and science competencies. In line with that, MI Manba'ul Huda has a goal in improving the quality of education through student management. Challenges and risks in making it happen are always there. Therefore, it is important for him to implement risk management in the institution. To conduct a risk management analysis on student management at MI Manba'ul Huda, the researcher used a qualitative descriptive method. Furthermore, the data obtained was through interviews with school principals, several educators, and education staff, in addition to which the researcher made direct observations at the school. The result of this study is that MI Manba'ul Huda has a strategy and mitigation in its efforts to overcome risks. As for other situations, these schools can accept the risks that occur to avoid greater risks.Keywords: Risk Management, Students, Quality of Education.